Developing an Integrated Process Safety Management Framework for Nickel Smelter Operations: Alignment of PP 50/2012, CCPS-RBPS, and OSHA 29 CFR 1910.119 - A. Yani Esbe; Irfan Bahiuddin (Jurnal Kesehatan Komunitas Indonesia, 2026)
The rapid expansion of Indonesia’s mineral processing and refining industry, particularly nickel smelters, has heightened the need for a systematic, risk-based Process Safety Management (PSM) program. Existing Occupational Health and Safety Management Systems under Government Regulation No. 50/2012 are considered insufficient to address the complex process hazards associated with smelter operations comprehensively. This study aimed to develop an integrated Process Safety Management (PSM) framework for PT Ceria Nugraha Indotama (PT CNI) that aligns with Government Regulation No. 50/2012, the Center for Chemical Process Safety Risk-Based Process Safety (CCPS-RBPS) framework, and OSHA 29 CFR 1910.119 requirements. A mixed-methods approach was employed. Qualitative data were collected through document reviews, field observations, focus group discussions, and in-depth interviews with operational personnel and management to identify implementation barriers and enabling factors. Quantitative data were collected from 101 purposively selected respondents, comprising internal personnel and external professionals from high-risk industries. An initial set of 22 PSM elements identified through cross-comparison analysis was consolidated into 12 integrated components through expert validation and focus group discussions. Data analysis included Pearson correlation validity testing, Cronbach’s Alpha reliability testing, Shapiro-Wilk normality testing, and One-Sample Wilcoxon Signed-Rank testing using Jamovi software. The Wilcoxon Signed-Rank Test showed significant positive responses across all twelve integrated components (W = 5151, p < 0.001), showing strong stakeholder acceptance of the proposed framework. Major implementation challenges included a limited understanding of trade secret management, mechanical integrity, and pre-startup safety review. In contrast, training systems, incident investigation practices, and work permit systems were identified as supporting factors. The integrated PSM framework developed in this study provides a practical reference for enhancing process safety performance in nickel smelters and other high-risk industries in Indonesia through a sustainable and risk-based management approach.